2003
DOI: 10.2151/jmsj.81.1273
|View full text |Cite
|
Sign up to set email alerts
|

Drastic Evening Increase in Precipitable Water Vapor over the Southeastern Tibetan Plateau

Abstract: A drastic increase in precipitable water vapor (PWV) in the evenings was repeatedly confirmed in October 2000, by an analysis of GPS observational data at Lhasa in the southeastern Tibetan Plateau, China. In order to investigate its mechanism, a numerical simulation was performed for a typical day using a regional atmospheric model. During the daytime, moisture is transported toward the summits of the Himalayas from the Hindustan plain along the southern slope of the mountain range by thermallyinduced upslope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A similar moisture convergence was repeated on 8 July. Using results of a numerical experiment of WV transport in October, Sasaki et al (2003) indicated that southerly upslope winds with a moist air mass in a valley of the Himalayas intruded into the southern TP, and general westerlies over the TP formed a stationary moisture front. Although they showed only the contribution of an upslope wind for WV intrusion, our simulation results suggest that the circulation pattern associated with the synoptic trough affected the distribution of WV over the southeastern TP.…”
Section: Transport Process Of Water Vapor Intruding Intomentioning
confidence: 99%
See 1 more Smart Citation
“…A similar moisture convergence was repeated on 8 July. Using results of a numerical experiment of WV transport in October, Sasaki et al (2003) indicated that southerly upslope winds with a moist air mass in a valley of the Himalayas intruded into the southern TP, and general westerlies over the TP formed a stationary moisture front. Although they showed only the contribution of an upslope wind for WV intrusion, our simulation results suggest that the circulation pattern associated with the synoptic trough affected the distribution of WV over the southeastern TP.…”
Section: Transport Process Of Water Vapor Intruding Intomentioning
confidence: 99%
“…Barros and Lang (2003) proposed a mechanism of nocturnal precipitation by a weakening of the nighttime valley wind, stagnating the WV in front of the Himalayas. Sasaki et al (2003) conducted numerical experiments to reveal the WV transport process over the south of TP during the post-monsoon season (October in 2000), and they showed that WV penetrated some cols of the Himalayas associated with a diurnal variation caused by a heating contrast between the TP and the Hindustan plain. At the same time, local circulation functioned to redistribute the precipitable water between the mountain and valley when there were weak general flows over the TP (Takagi et al 2000;Kuwagata et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Yanai and Li (1994) noted that a vertical circulation and associated convective activity over and around the TP in the summer are maintained by a thermally induced plateau-scale circulation that is driven by thermal contrasts between the plateau and surrounding regions. Sasaki et al (2003) used results from a numerical model and showed that diurnal variations in precipitable water (PW) at Lhasa (29.7°N, 91.1°E) in October were associated with a plateau-scale diurnal circulation system. Recent studies have discussed the relationship between convection (or precipitation) and topography over the TP during summer.…”
Section: Introductionmentioning
confidence: 99%
“…In the diurnal cycle, the effects of precipitation vary at different times and with different precipitation amount (Burns et al, 2015; Hamm et al, 2023; Zhang et al, 2021). Night‐time precipitation is a widespread and unique phenomenon in the TP (Du et al, 2007; Sasaki et al, 2003; Wang et al, 2018b; Yu et al, 2011). Variations in night‐time precipitation in the TP occur with changes in monsoon patterns (Ueno et al, 2009).…”
Section: Introductionmentioning
confidence: 99%